Perceptions of academic staff on research and publishing in Kenyan universities - Migosi, Joash; Muola, James Muthee; Maithya, Redempta (International Journal of Education Administration and Policy Studies, 2012)
Academic research represents the backbone of human activity in improving the quality of life through expanding frontiers of academic knowledge, and making further research possible throughout the world. Academic research aims at providing solutions for many current problems. Research is a vital and necessary part of modern university education, where universities are perceived to be producers of new knowledge. The Kenya government is restructuring tertiary education with a view to re align it to the country’s economic blue print, the vision 2030, and the new constitution. This calls for universities to be more innovative and research focused. Universities that do not build and strengthen their research capacity will be severely restricted hence; academics must carry out more research and publish. This study was designed to assess the perceptions of academic staff in Kenyan universities towards research and publishing, and to find out if the expressed perceptions were influenced by academic staff’s characteristics such as gender, type of university, age group, rank, highest degree obtained, years since last highest degree was obtained and associated university. Survey research design was employed in this study. The questionnaire was used to collect information from university academic staff drawn from 11 public and private universities. Seven hypotheses were tested. The information was analyzed by use of descriptive statistics. Scientific package for social sciences (SPSS, Version 15) was used to analyse descriptive statistics while analysis of variance (ANOVA) was used in hypothesis testing. The results obtained from this study indicate that there was a lower perception towards research and publishing by younger generation lecturers compared to the older academics. The main recommendation made by this study is for each individual university to be encouraged to foster a deliberate positive research and publishing culture in their institutions.
Keywords: Research productivity; Publication productivity; Universities; Perception.